Analisis kemampuan guru dalam memanfaatkan media pembelajaran berbasis teknologi informasi dan komunikasi pada pembelajaran ipas kelas iv di sekolah dasar - Yustika, Arvenia; Istiyati, Siti; Adi, Fadhil Purnama (Universitas Sebelas Maret, 2025)
This research aims to describe teachers' abilities in utilizing Information and Communication Technology (ICT)-based learning media in class IV science learning at SDN Kleco I Surakarta. This research used descriptive qualitative approach with a case study type of research. Sampling in this study used a purposive sampling technique. Data collection techniques used tests, observation, interviews and document study. Data were obtained from class IVA, IVC and IVD teachers at SDN Kleco I Surakarta. The validity test technique used time triangulation and technique triangulation. The data analysis technique used is the Miles and Huberman model with stages of data collection, data reduction, data presentation, drawing conclusions and data verification. The results of this research are that theoretically teachers' knowledge regarding ICT learning media is included in the